Sejarah Institut Perguruan Tinggi Ilmu Al-Qur’an (PTIQ) Jakarta dan Sumbangannya Dalam Pengajian Al-Qur’an di Indonesia: History of the Jakarta Higher Institute of Qur'anic Sciences (PTIQ) and its Contribution to Qur'anic Studies in Indonesia - Achmad, Nurjanah; Abdullah, Mustaffa; Mohamed Adnan, Mohamad Azrien (Journal Al-Muqaddimah, 2022)
The Quranic studies in Indonesia has been rapidly evolving since Islam arrived in the archipelago. It continues to develop into the final stage of formal education, namely Islamic higher education. Thus, this research aims to explore the history of PTIQ Jakarta Institute which is a leading institution in the field of the Qur’an and its contribution to Quranic studies in Indonesia. Using a document analysis approach, this research found that Quranic studies in department of Qur’anic Studies and Tafsir (IAT) at PTIQ has its own uniqueness. It maintains the old tradition of reading classical literature from earlier scholars but also does not abandon contemporary studies. In fact, the Quranic studies which offered has also received recognition as well as providing various meaningful contributions to Muslims community in Indonesia, such as community service and publication of scholarly works. However, since its establishment until now, PTIQ has continued to transform into an authoritative centre for Qur’anic studies at national and international levels.